Psychological disadaptation as a cause of dissatisfaction with sexual life - Norkina, I. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article presents the view on the problem of psychological maladaptation as a factor of dissatisfaction with sexual life, which is manifested in the disclosure of the data of the concepts, descriptions and characteristic features that are manifested in these concepts. The psychological aspects of the manifestation of psychological maladaptation and sexual dissatisfaction are revealed, and an empirical study of the relationship between psychological maladaptation and sexual dissatisfaction was conducted. Sexual and psychological relationships are caused by a determinant relationship (have their internal causes and external effects), this in turn indicates that sex life has an impact on interpersonal, intimate relationships among partners, and can also serve as a cause of the psychological defining of the individual. An important aspect was the sexual satisfaction with its physiological and psychological components, and the special role of various manifestations of feelings (mood, anxiety, emotions, stresses) on the sexual function of the individual was proved. The result of the study is the significance of the statistical relationship between psychological maladaptation and sexual dissatisfaction. This means that the psychological state of a person has a great influence on sexual life and vice versa, the sexual sphere of human life provides a certain amount of filling and general mental background state of personality in any life situations. With the help of theoretical and empirical analysis we received the following results: high indicators of sexual satisfaction and realized evidence of the ability of a person to feel pleasure during sexual intercourse, to control their own sexual behavior In accordance with the norms of social and personal ethics. Such a person is free of fear, a sense of shame and guilt, false representations and other psychological factors that inhibit sexual response and violate sexual relations.
Keywords: personality; psychological maladaptation; sexuality; sexual dissatisfaction; adaptive possibilities